2022
DOI: 10.4285/kjt.22.0029
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac evaluation for end-stage kidney disease patients on the transplant waitlist: a single-center cohort study

Abstract: Background: Cardiac evaluation before deceased donor kidney transplant (DDKT) remains a matter of debate. Data on Asian countries and countries with prolonged waiting times are lacking. This study aimed to assess the outcomes of patients referred for DDKT after a cardiac evaluation at an Asian tertiary transplant center. Methods: This single-center retrospective review analyzed patients who were referred for waitlist placement and underwent cardiac stress testing between January 2009 and December 2015. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Kidney transplant recipients (KTRs) are not only at increased risk of immunosuppression-related adverse events (iRAEs), such as infections, malignancy and metabolic complications from chronic immunosuppression exposure, but are also at risk of graft loss from rejection with underimmunosuppression 1–4. Within our KTR cohort, infections accounted for 41.4% of all deaths and 35.7% of all hospital admissions 1.…”
Section: Introductionmentioning
confidence: 99%
“…Kidney transplant recipients (KTRs) are not only at increased risk of immunosuppression-related adverse events (iRAEs), such as infections, malignancy and metabolic complications from chronic immunosuppression exposure, but are also at risk of graft loss from rejection with underimmunosuppression 1–4. Within our KTR cohort, infections accounted for 41.4% of all deaths and 35.7% of all hospital admissions 1.…”
Section: Introductionmentioning
confidence: 99%
“…It was also speculated that screening for CAD may contribute to delays in listing patients for transplant [ 9 ]. On the other hand, we observed that clinical stratification helps to identify patients who may benefit from non-invasive coronary evaluation [ 13 ]. Risk stratification based on myocardial stress testing was useful only in patients with an intermediate risk for events, but failed in patients at low and high risk.…”
Section: Introductionmentioning
confidence: 99%